Innovation in the Global Firm - Bilir, L. Kamran; Morales, Eduardo (Journal of Political Economy, 2020)
How global are the gains from innovation? When firms operate plants in multiple countries, technological improvements developed in one location may be shared with foreign sites for efficiency gain. We develop a model that accounts for such transfer and apply it to measure returns to R&D investment for a panel of US multinationals. Our estimates indicate that innovation increases performance at firm locations beyond the innovating site: the median multinational firm realizes abroad 20% of the return to its US R&D investment, revealing a spatial disconnect between the costs and potential gains of policies that encourage multinationals’ US innovation.